Mapping VR, AR, and AI-Based Mental Health Interventions: A Bibliometric Analysis, 1996–2024 - Saky, Sheikh Abu Toha Md; Azani, Mohammad Zakki; Islam, Md Nurul (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This study maps the development, scholarly impact, thematic structure, and international collaboration patterns of research on virtual reality (VR)-, augmented reality (AR)-, and artificial intelligence (AI)-based mental health interventions. Bibliographic records were retrieved from Scopus on November 7, 2024, and analyzed using Biblioshiny. The dataset comprised 282 documents published between 1996 and 2024; therefore, the 2024 publication count represents partial-year coverage. Descriptive performance analysis, citation analysis, co-authorship analysis, keyword co-occurrence mapping, and topic-trend analysis were applied. The literature showed an annual growth rate of 14.47%, an average of 25.94 citations per document, and an international co-authorship rate of 19.15%. The United States, the United Kingdom, and Italy were prominent contributors, whereas Africa, South America, and many low- and middle-income countries remained underrepresented. The citation and thematic structures were dominated by VR, particularly virtual reality exposure therapy for posttraumatic stress disorder, anxiety, and phobias. AR- and AI-related therapeutic applications were included in the broader research landscape but were less prominent in the mapped networks and influential-document rankings. By examining VR, AR, and AI within a single bibliometric framework, this study identifies imbalances in technological maturity, therapeutic focus, and global research participation. Future progress requires stronger clinical validation, transparent and reproducible methods, culturally adapted interventions, ethical governance, cost-sensitive implementation, and more equitable international collaboration.